Hypoxia induces downregulation of soluble guanylyl cyclase β(1) by miR-34c-5p - Xu, Xiaojian (The Company of Biologists, 2012)
Soluble guanylyl cyclase (sGC) is the principal receptor for nitric oxide (NO) and crucial for the control of various physiological functions. The β(1) subunit of sGC is obligatory for the biological stability and activity of the sGC heterodimer. MicroRNAs (miRNAs) are important regulators of gene expression and exert great influences on diverse biological activities. The aim of the present study was to determine whether or not the expression of sGCβ(1) is specifically regulated by miRNAs. We report that miR-34c-5p directly targets sGCβ(1) under hypoxia. Bioinformatics analysis of the sGCβ(1) 3′-untranslated region (3′-UTR) revealed a putative binding site for miR-34b-5p and miR-34c-5p, but only miR-34c-5p inhibited luciferase activity through interaction with sGCβ(1) 3′-UTR in HEK293T cells. Site-directed mutagenesis of the putative miR-34c-5p binding site abolished the negative regulation of luciferase expression. Overexpression of miR-34c-5p repressed the expression of sGCβ(1) in stable cell lines, which was reversed by miR-34c-5p-specific sponge. Inoculation of mouse lung tissues in vitro with lentivirus bearing miR-34c-5p significantly decreased both the expression of sGCβ(1) and NO-stimulated sGC activity, which was also rescued by miR-34c-5p-specific sponge. Furthermore, we identified the putative Sp1-binding site in the promoter region of miR-34c-5p. Luciferase reporter constructs revealed that Sp1 directly binds to the wild-type promoter of miR-34c-5p, which was confirmed by chromatin immunoprecipitation. In summary, these findings reveal that miR-34c-5p directly regulates sGCβ(1) expression, and they identify the key transcription factor Sp1 that governs miR-34c-5p expression during hypoxia.